Clinical characteristics, management approaches, and outcomes of patients with heart failure: the Jordan Heart Failure Registry - Abu-Hantash, Hadi; Khader, Yousef; AL-Saleh, Akram; Al-Makhamreh, Hanna; Ibdah, Rasheed; Ababneh, Muhannad; Nammas, Asem; Rasheed, Amr; Toubasi, Ahmad; Al-Qalalweh, Sarah; Mahmoud, Mohammad Y.; Albustanji, Farah; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHeart failure (HF) is a complex clinical syndrome with diverse etiologies and pathophysiological mechanisms. While chronic HF has gained substantial understanding, acute HF remains less elucidated. This study aimed to analyze the data from the Jordanian Heart Failure Registry (JoHFR) to assess the clinical characteristics, management approaches, and outcomes of patients with HF.MethodsThe study included data from 21 healthcare centers from private sector clinics and hospitals and public secondary and tertiary university hospitals across Jordan from July 1, 2021, to February 28, 2023. It included patients above the age of 18 with chronic HF, acute decompensated HF de novo, or acute on top of chronic HF. Data encompassed patient demographics, comorbidities, medications, clinical presentation, laboratory findings, echocardiograms, and outcomes.ResultsA total of 2,151 patients were enrolled. More than half (58.0%) of the study cohort were males. The mean age of patients was 66 years, with almost half of the patients (45.5%) aged 70 or older. Chronic HF accounted for 71% of cases, while acute HF constituted 29% of cases. Obesity was identified in 36.6% of the cohort. Hypertension (80.7%) and a history of atherosclerotic cardiovascular disease (ASCVD) (80.6%) were the most prevalent comorbidities. Beta-blockers were the most commonly prescribed medications (67.4%). RAAS inhibitors including ACE inhibitors (18.1%), ARBs (25.2%), and ARNI (10.8%), were also frequently used. Dyspnea (85.9%) was the most common presenting symptom, and elevated B-type natriuretic peptide levels were well utilized and observed in most patients (96.7%). Left ventricular ejection fraction (LVEF) was ≤40% in 58.8%, 41%–49% in 11.4%, and ≥50% in 29.7% of patients, with a mean (SD) of 38.1% (12.7%). The in-hospital mortality rate in our registry stood at 9.6%.ConclusionThe Jordan Heart Failure Registry (JoHFR) presents the unique characteristics of both chronic and acute HF patients in Jordan and highlights areas for improving patient care and adherence to international guidelines. These findings should guide healthcare policymakers and practitioners in the country to enhance the quality of management of HF patients and implement interventions to reduce the burden of comorbidities accompanying HF.